A qualitative study examining the impact of COVID-19 on capacity for sustainability of tobacco control programs - Jessica Gannon; Sarah Moreland-Russell (BMC, 2024)
Abstract Background The coronavirus (COVID-19) pandemic presented a significant stressor on the public health system in the United States. While we know the immediate effects of the pandemic on public health programming, no literature has examined the resultant long-term impact on programmatic capacity for sustainability. This paper aims to identify the impact that the COVID-19 pandemic had on state tobacco control program's capacity for sustainability. Methods From December 2018 to January 2022, we conducted 46 technical assistance calls with tobacco control program employees from 11 states. Calls were audio recorded and professionally transcribed. We analyzed calls (n = 20) that took place during the COVID-19 pandemic. Thematic analysis focused on the impact the COVID-19 pandemic had on tobacco control program's capacity for sustainability. Results We identified six domains of sustainability that were impacted by COVID-19: (1) funding stability; (2) organizational capacity; (3) partnerships; (4) communication; (5) strategic planning; and (6) program adaptation. Conclusions Our study is the first to identify the impact of the pandemic on capacity for sustainability of tobacco control programs. Having an understanding of COVID-19's influence on these sustainability domains could help with future public health programming during significant public health events and emergency preparedness. ClinicalTrials.gov Identifier NCT03598114. Registration date Retrospectively registered 02-07-2018.